Palliative Care Conversations for Heart Failure Nurses: A Pilot Education Intervention - Stephanie Turrise PhD, RN-BC, APRN, CNE, CHFN-K, FAHA; Caroline A. Jenkins BSN, RN; Tamatha Arms PhD, DNP, PMHNP-BC, NP-C; Andrea L. Jones PhD, MSW, LSW (SAGE Open Nursing, 2021)
Introduction Heart failure is a progressive condition affecting 6.2 million Americans. The use of palliative and supportive care for symptom management and improved quality of life is recommended for persons with heart failure. However, 91% of nurses believe they need further training to have palliative care conversations. The purpose of this pilot education intervention was to determine if providing nurses with education on the timing and content of palliative care conversations would improve their perceived skill and knowledge. Methods This was a pilot study of an online educational intervention. Data were electronically collected from 13 participants using validated questionnaires delivered via Qualtrics. Participants completed a demographic survey and End-of-Life Professional Caregiver Survey (EPCS) before and after completing an online, asynchronous education module. Results Mean scores were higher on all posttest measures. Independent samples t -tests revealed statistically significant differences on the Effective Care Delivery (ECD) scale ( t [32] = −2, p  = .05) and total EPCS scale scores ( t [32] = −2.2, p  = .03) from pre- to posttest. Conclusion Scores increased on all dimensions pretest to posttest with statistically significant differences in ECD and total scores. Providing asynchronous online education on timing and content of palliative care conversations to nurses caring for people with heart failure is a feasible and effective way to improve perceived knowledge and skill of palliative care conversations.